Heat Stress Weakens the Skin Barrier Function in Sturgeon by Decreasing Mucus Secretion and Disrupting the Mucosal Microbiota - Yang, Shiyong; Xu, Wenqiang; Tan, Chaolun; Li, Minghao; Li, Datian; Zhang, Chaoyang; Feng, Langkun; Chen, Qianyu; Jiang, Jun; Li, Yunkun; Du, Zongjun; Luo, Wei; et al. (Frontiers in Microbiology, 2022)
Heat stress induced by global warming has damaged the well-being of aquatic animals. The skin tissue plays a crucial role as a defense barrier to protect organism, however, little is known about the effect of heat stress on fish skin, particularly in cold-water fish species. Here, we investigated the effects of mild heat stress (24°C, MS) and high heat stress (28°C, HS) on Siberian sturgeon skin using RNA-seq, histological observation, and microbial diversity analysis. In RNA-seq, 8,819 different expression genes (DEGs) in MS vs. C group and 12,814 DEGs in HS vs. C group were acquired, of which the MS vs. C and HS vs. C groups shared 3,903 DEGs, but only 1,652 DEGs were successfully annotated. The shared DEGs were significantly enriched in pathways associating with mucins synthesis. Histological observation showed that the heat stresses significantly reduced the number of skin mucous cells and induced the damages of epidermis. The microbial diversity analysis elicited that heat stress markedly disrupted the diversity and abundance of skin microbiota by increasing of potential pathogens (Vibrionimonas, Mesorhizobium, and Phyllobacterium) and decreasing of probiotics (Bradyrhizobium and Methylovirgula). In conclusion, this study reveals that heat stress causes adverse effects on sturgeon skin, reflecting in decreasing the mucus secretion and disordering the mucosal microbiota, which may contribute to develop the preventive strategy for heat stress caused by global warming.